Quality Education with Sustainable Development Goals (SDGs) No 4: Knowledge-based - Chotibuddin, M.; Zunaih, Ahmad Iwan; ., Musbikhin; ., Nashihin (Journal of Ecohumanism, 2025)
This study evaluates the quality of knowledge-based education in favourite high schools in East Java and how it relates to SDGs goal 4 on quality and inclusive education. Using qualitative and quantitative methods, including curriculum analysis, direct observation and interviews with principals, teachers and students, this study reveals how the knowledge-based curriculum is implemented, the role of leadership in driving innovation and efforts to address access gaps. The findings show that these schools are effective in developing analytical and critical thinking skills through visionary leadership and inclusive learning environments. However, there are access gap challenges that require special attention. Managerial implications highlight the need for policies that support inclusive education, adaptive curriculum development and equalisation of educational technology to achieve SDGs No. 4 and support sustainable development in the future.